2018
DOI: 10.1097/sle.0000000000000541
|View full text |Cite
|
Sign up to set email alerts
|

Early Results of Laparoscopic Sleeve Gastrectomy With Loop Bipartition

Abstract: TLB-SG is a more effective and simpler method, becoming a candidate for being the most frequently performed surgical operation, in the field of metabolic surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
14
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 11 publications
1
14
1
Order By: Relevance
“…Our results demonstrated a similar T2DM remission rate (71%) with the same operation. We had reported this rate as 66.6% at the 3-month evaluation 16 …”
Section: Discussionmentioning
confidence: 84%
“…Our results demonstrated a similar T2DM remission rate (71%) with the same operation. We had reported this rate as 66.6% at the 3-month evaluation 16 …”
Section: Discussionmentioning
confidence: 84%
“…This was in line with the findings of Khalaf et al (8) and Romero et al (10) who found that the average operating time for the SASI operation was 98.8 minutes and 116.3 minutes, respectively (range, 60-270 minutes). The SASJ method was shown to have a significantly longer operating time in different research by Arslan et al (11) with a mean value of 192.8 minutes.…”
Section: Discussionmentioning
confidence: 93%
“…Arslan et al (11) observed a substantial drop in glycosylated haemoglobin levels three months after SASJ surgery, from 9.58 to 6.56%.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…The SG + TB technique was first developed by Santoro et al, and after the publication of the results of 1020 patients in 2012, surgeons in the field of obesity and metabolic surgery became very interested in it [7,8]. This technique serves as an important alternative to ileal interposition surgery, which has greater metabolic effect but is more aggressive [9]. In the present study, we compared the use of LS and CS GI in SG + TB in terms of early and late perioperative and postoperative status.…”
Section: Discussionmentioning
confidence: 99%